Indolo[2,3-a]quinolizidines and Derivatives: Bioactivity and Asymmetric Synthesis - Perez, Maria; Espadinha, Margarida; M. M. Santos, Maria (Current Pharmaceutical Design, 2015)
Corynantheine alkaloids with a tetracyclic indole[2,3-a]-quinolizidine motif are an important issue in academia and in the life science industries due to their broad bioactivity profile. In particular, the main biological effects described for indoloquinolizidines include analgesic, anti-inflammatory, antihypertensive, and antiarrhythmic activities, as well as inhibition of multiple ion channels, affinity for opioid receptors, and activity against Leishmania. For that reason, in the last decades, numerous efforts have been invested in the development of novel synthetic strategies to obtain the indole[2,3-a]-quinolizidine system. This review focuses on the synthetic methodologies developed to target the most important alkaloids of this family, and highlights the potential use of these alkaloids or analogs to treat several diseases, ranging from cancer to neurodegenerative disorders.
Keywords: Indoloquinolizidines